Book spreaders in the towns of Samogitian principality in the XVIII century - Meilus, Elmantas (Knygotyra, 2024)
The free spread of Enlightenment books from Western Europe in the 18th century in the Samogitian principality (the books were presumably spread following the decision of sovereign Michał Korybut Wiśniowiecki issued in 1672) worried the leaders of the Catholic Church who were responsible for education in the Republic of Both Nations. For this reason, in 1743, the Samogitian bishop Antanas Tiškevičius banned the free book trade in his diocese and commissioned Juozas Stripeika and Martynas Maulevičius, living in Kražiai, with the task of regulating book selling. Antanas Tiškevičius' circular provides the following information: 1. In the 18th century, at least in its 2nd quarter, the book trade was a profitable business, which means that books were popular; 2. It is likely that until the mentioned time, books had been sold by traveling book sellers for whom that was their only occupation; 3. At the considered time, Samogitia received the most up-to-date literature from Western Europe.From the circular of 1774, we learn that books were not only sold at special places. They were delivered by agents throughout the whole principality. There was permission to sell not only books not banned by the Catholic Church but also holy pictures and other items necessary for religious rites. It was noted that all wares would be confiscated from those who were engaged in book selling without permission. In this way, Kražiai turned into the Samogitian trade center for books and religious articles.The aforementioned M. Maulevičius was engaged in book trade and other cultural activities until 1783-1784. Besides M. Maulevičius and J. Stripeika, books in Kražiai were also sold by the husband and wife Daubarai (1751-1769) and Juozapas and Grigas Dziedzickiai (1774-1784). In the 2nd half of the 18th century, people engaged in book spreading could also be found in some other Samogitian towns, e.g., in Seda, four such persons sold books at the time. Most Samogitian book sellers used to purchase for resale some hundreds and even thousands of copies of books of various denominations (religious, textbooks; mostly in Lithuanian and Polish) in Vilnius and, presumably, some other towns.There is no data available on the trade of Jewish books. However, there is no doubt that it existed in Samogitia because in descriptions of Jewish property after fires, we may find some mentions of larger or smaller collections of Jewish books. Besides, throughout the whole 18th century, there are mentions of Jewish bookbinders who obviously served not only their fellow countrymen but Christians as well.The above-presented short review reveals that in the 2nd half of the 18th century, the book trade in Samogitia—concentrated in Kražiai—was a profitable business in which some families were engaged. The books for sale were numerous and varied. The bookbinder trade was in great demand. The mentioned evidence proves that by the second half of the 18th century, a social stratum of book consumers had developed in Samogitia.
Keywords: -